2001
DOI: 10.1034/j.1600-079x.2001.300201.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, mitochondria, and cellular bioenergetics

Abstract: Aerobic cells use oxygen for the production of 90-95% of the total amount of ATP that they use. This amounts to about 40 kg ATP/day in an adult human. The synthesis of ATP via the mitochondrial respiratory chain is the result of electron transport across the electron transport chain coupled to oxidative phosphorylation. Although ideally all the oxygen should be reduced to water by a four-electron reduction reaction driven by the cytochrome oxidase, under normal conditions a small percentage of oxygen may be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
316
1
12

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(336 citation statements)
references
References 43 publications
7
316
1
12
Order By: Relevance
“…These data agree with he interaction between melatonin and striatal D 1 /D 2 receptors elsewhere reported with electrophysiological approaches [18]. Experiments in vivo and in vitro have shown that melatonin promotes mitochondrial phosphorylation and ATP synthesis interacting with the electron transport chain complexes I and IV [5,[37][38][39]. These effects are related to the antioxidant role of melatonin, since it scavenges hydrogen peroxide [53] and increases mitochondrial GSH levels, counteracting the oxidative stress-induced mitochondrial damage [37].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These data agree with he interaction between melatonin and striatal D 1 /D 2 receptors elsewhere reported with electrophysiological approaches [18]. Experiments in vivo and in vitro have shown that melatonin promotes mitochondrial phosphorylation and ATP synthesis interacting with the electron transport chain complexes I and IV [5,[37][38][39]. These effects are related to the antioxidant role of melatonin, since it scavenges hydrogen peroxide [53] and increases mitochondrial GSH levels, counteracting the oxidative stress-induced mitochondrial damage [37].…”
Section: Discussionsupporting
confidence: 87%
“…These effects are related to the antioxidant role of melatonin, since it scavenges hydrogen peroxide [53] and increases mitochondrial GSH levels, counteracting the oxidative stress-induced mitochondrial damage [37]. These data, with those reporting an effect of melatonin on mitochondrial inner membrane fluidity [22], further support that mitochondria are an important target for melatonin action [2,5].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Melatonin also increased the production of ATP in control mitochondria. Acuña-Castroviejo et al documented that melatonin counteracted mitochondrial oxidative damage induced by t-butyl hydroperoxide, recovering glutathione levels and ATP production [45,46] . These data, along with other findings, suggest that melatonin regulates mitochondrial homeostasis [47] .…”
Section: Discussionmentioning
confidence: 99%